Die Lösung einer elliptischen Gleichungsystem - Šileris, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. В. Шилeрис. Решение системы уравнений эллиптического типа V. Šileris. Elipsinio tipo lygčių sistemos sprendimas